2018
DOI: 10.5539/mas.v12n9p221
|View full text |Cite
|
Sign up to set email alerts
|

Study of Moisture Budget of Meteorological Droughts over Indian Region

Abstract: The study mainly focuses on heat and moisture budget components and its variations during meteorological drought conditions over India for the period 1951-2013. IITM sub-divisional summer monsoon standardized rainfall anomaly is considered to identify the meteorological drought where the standardized summer monsoon rainfall anomaly is less than one. From the analysis, there are thirteen meteorological droughts are identified, and the rainfall decreased on spatial and temporal scales with significant changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Self‐healing materials can protect the film surfaces against external mechanical forces autonomously by repairing the mechanical damage during their usage for various applications. [ 44–48 ] Self‐healing materials can be utilized either as a thin film on top of conventional GDBFs or as a substrate for developing stretchable and completely self‐healable gas barrier films. For instance, Song et al developed a self‐healable oxygen barrier film using 8 bilayers of polyethyleneimine (PEI) and polyacrylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐healing materials can protect the film surfaces against external mechanical forces autonomously by repairing the mechanical damage during their usage for various applications. [ 44–48 ] Self‐healing materials can be utilized either as a thin film on top of conventional GDBFs or as a substrate for developing stretchable and completely self‐healable gas barrier films. For instance, Song et al developed a self‐healable oxygen barrier film using 8 bilayers of polyethyleneimine (PEI) and polyacrylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group is investigating these aspects of purification of polluted water and found some successful methods for the extraction of F -, Pb 2+ , Cr (VI), NO2 -, NH3, PO4 3and Dyes. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] While we are investigating different bio-materials of the different plant as adsorbents for the extraction of different pollutive ions, stems of Cassia Occidentalis plant are noted to have good adsorption nature towards Al (III) ions. Hence, in this work, an adsorbent derived from Cassia Occidentalis plant stems is investigated for its adsorption nature towards Al (III) ions by optimizing the various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These non-conventional adsorbents are proving to be effective and economical and are suitable especially in agricultural countries like India [15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Our research group is investigating these aspects of pollution control methods and found some successful adsorbents for various toxic ions [25][26][27][28][29][30][31][32][33][34][35] . In our initial search among the various bio-materials, bark powder of Ziziphus mauritiana plant is found to adsorb Chromate ions from water.…”
Section: Introductionmentioning
confidence: 99%